(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: To find out the incidence and etiology of ventilator-associated pneumonia (VAP) in pediatric intensive care unit. Subjects and methods: Descriptive study of 173 patients requiring mechanical ventilator ≥ 48 hours at Nghe An Obstetrics and Pediatrics Hospital from August 2020 to July 2022. Results: 47 patients suffered ventilator-associated pneumonia with 51 episodes met the criteria for VAP. The incidence rate reached up to 27,1% and 30,9/1000 mechanical ventilator days. The most frequently isolated mico-organisms were Acinetobacter baumannii (29,7%), followed by Klebsiella pneumoniae (22,2%) and Pseudomonas aeruginosa (18,5%). By compared with nonVAP group, VAPs were closely related to longer ventilator, intensive care unit stay time and hospitalization time. Conclusions: The incidence of VAP in this study was relatively high, strict supervision of infection control protocols are crucial.